2022
DOI: 10.3389/fpsyg.2022.995981
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in life, meaning-making and posttraumatic growth in cancer patients: Systematic review and meta-analysis

Abstract: IntroductionThe purpose of this systematic review and meta-analysis is to assess the association between meaning in life (MiL), meaning-making and posttraumatic growth (PTG) in the context of cancer.MethodsA systematic search was conducted in eighteen electronic databases. The screening and selection process followed the PRISMA guidelines. For the purpose of the meta-analysis, the correlation coefficients between meaning in life and posttraumatic growth were extracted from the included studies. The effect size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…Moreover, patients who reappraised their personal values reported higher scores in personal meaning, self‐transcendence, achievement, self‐direction, stimulation, and physical well‐being compared to those who did not change their personal values but still exhibited valued living. These findings highlight the intrinsic connection between meaning adaptation, meaningfulness, quality of life, and personal growth, aligning with previous studies emphasizing the role of meaning in life in PTG 31 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, patients who reappraised their personal values reported higher scores in personal meaning, self‐transcendence, achievement, self‐direction, stimulation, and physical well‐being compared to those who did not change their personal values but still exhibited valued living. These findings highlight the intrinsic connection between meaning adaptation, meaningfulness, quality of life, and personal growth, aligning with previous studies emphasizing the role of meaning in life in PTG 31 …”
Section: Discussionsupporting
confidence: 91%
“…These findings highlight the intrinsic connection between meaning adaptation, meaningfulness, quality of life, and personal growth, aligning with previous studies emphasizing the role of meaning in life in PTG. 31 Importantly, meaning adaptation was also associated with physical well-being. Many cancer patients placed increased emphasis on physical self-care as part of their adapted values, potentially leading to improved physical well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies examining posttraumatic growth during cancer treatment and in survivorship also examine and review similar terms referring to personal growth after diagnosis and/or treatment where clear associations are shown. 61,70…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they found that those who experienced a better quality-of-life at the end of life reported significantly higher posttraumatic growth, a finding reported in several previous studies among people with and surviving cancer. 61,76…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation